2016
DOI: 10.1155/2016/5829063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Redox and Glucose‐Dependent Txnip Protein Interactions

Abstract: Thioredoxin-interacting protein (Txnip) acts as a negative regulator of thioredoxin function and is a critical modulator of several diseases including, but not limited to, diabetes, ischemia-reperfusion cardiac injury, and carcinogenesis. Therefore, Txnip has become an attractive therapeutic target to alleviate disease pathologies. Although Txnip has been implicated with numerous cellular processes such as proliferation, fatty acid and glucose metabolism, inflammation, and apoptosis, the molecular mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Compared to the control cones without Txnip transduction, the intensity of mitoRFP was higher in P20 rd1 cones transduced with Txnip (Figure 5 -figure supplement 1C,D). A previous study identified 15 proteins that interact with Txnip.C247S (Forred et al, 2016). Among these interactors was Parp1, which can negatively affect mitochondria through deleterious effects on the mitochondrial genome (Hocsak et al, 2017;Szczesny et al, 2014), as well as effects on inflammation and other cellular pathways (Fehr et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the control cones without Txnip transduction, the intensity of mitoRFP was higher in P20 rd1 cones transduced with Txnip (Figure 5 -figure supplement 1C,D). A previous study identified 15 proteins that interact with Txnip.C247S (Forred et al, 2016). Among these interactors was Parp1, which can negatively affect mitochondria through deleterious effects on the mitochondrial genome (Hocsak et al, 2017;Szczesny et al, 2014), as well as effects on inflammation and other cellular pathways (Fehr et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…5c,d). A previous study identified 15 proteins that interact with Txnip.C247S (Forred et al, 2016). Among these interactors was Parp1, which can negatively affect mitochondria through deleterious effects on the mitochondrial genome (Hocsak et al, 2017;Szczesny et al, 2014), as well as have effects on inflammation and other cellular pathways (Fehr et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Another partner interaction suggested by previous studies and explored here is the interaction with HSP90AB1 ( Figure 5 ). HSP90AB1 interacts with both the wt and C247S alleles (Forred et al, 2016). Little is known about the function of HSP90AB1.…”
Section: Discussionmentioning
confidence: 99%